THE RIGHTS OF FREEDOM ASSOCIATION AFTER CHANGES A COMMUNITY ORGANIZATION LAW IN INDONESIA - Munir, Sirajul; Ilham, Lailul (JURNAL SETIA PANCASILA, 2022)
Law Number 16 of 2017 concerning Social Organizations was formed in the context of recognizing Human Rights (HAM), namely the freedom of association, assembly and expression of opinion. Recognition of human rights needs to be regulated in a balanced manner so as not to threaten state sovereignty. This study uses a normative juridical method with the following approaches: conceptual approach, and statute approach. The results of the study show that Law Number 16 of 2017 concerning Social Organizations uses the contrarius actus principle in the mechanism for revocation of legal entity status. This was chosen to be more effective and efficient in balancing the right to association and the preservation of the Pancasila ideology and the 1945 Constitution of the Republic of Indonesia.